Effect of fluorocarbon chains on the mesomorphic properties of chiral imines and their complexes with copper(II) - Ocak, Hale; Bilgin-Eran, Belkiz; Tschierske, Carsten; Baumeister, Ute; Pelzl, Gerhard (ROYAL SOC CHEMISTRY, 2009)
The synthesis and mesomorphism of new chiral imine compounds incorporating a fluorocarbon chain which have calamitic molecular shape and their complexes with copper(II) are reported. The liquid crystalline properties were investigated using polarised optical microscopy, differential scanning calorimetry and X-ray diffraction. Imine compounds with a semifluorinated chain and a short chiral chain show chiral smectic mesophases with dramatically enhanced mesophase stabilities compared to the related hydrocarbon derivatives. In addition, the first examples of mesogenic chiral salicylaldiminate copper(II) complexes carrying semifluorinated alkyl chains at their peripheries have been synthesized and their liquid crystalline properties were investigated.
Keywords: LIQUID-CRYSTALLINE PROPERTIES; MICRO-SEGREGATION; BLOCK MOLECULES; COLUMNAR; LAMELLAR; LIGANDS; RHENIUM(I); MESOPHASES; MESOGENS; DESIGN; Chemistry; Materials Science